Complete genome analysis reveals evolutionary history and temporal dynamics of Marek’s disease virus - Li, Kai; Yu, Zhenghao; Lan, Xingge; Wang, Yanan; Qi, Xiaole; Cui, Hongyu; Gao, Li; Wang, Xiaomei; Zhang, Yanping; Gao, Yulong; Liu, Changjun (Frontiers in Microbiology, 2022)
Marek’s disease has caused enormous losses in poultry production worldwide. However, the evolutionary process and molecular mechanisms underlying Marek's disease virus (MDV) remain largely unknown. Using complete genomic sequences spanning an unprecedented diversity of MDVs, we explored the evolutionary history and major patterns in viruses sampled from 1964 to 2018. We found that the evolution of MDV strains had obvious geographical features, with the Eurasian and North American strains having independent evolutionary paths, especially for Asian strains. The evolution of MDVs generally followed a clock-like structure with a relatively high evolutionary rate. Asian strains had evolved at a faster rate than European strains, with most genetic mutations occurring in Asian strains. Our results showed that all recombination events occurred in the UL and US subregions. We found direct evidence of a closer correlation between Eurasian strains, related to a series of reorganization events represented by the European strain ATE2539. We also discovered that the vaccine strains had recombined with the wild virulent strains. Base substitution and recombination were found to be the two main mechanisms of MDV evolution. Our study offers novel insights into the evolution of MDVs that could facilitate predicting the spread of infections, and hence their control.